Keragaan Nomor Harapan Lada Hibrida LH 20-4 Tahan Penyakit BPB di lampung Timur - Ilham Nur Adhi Wicaksono; Rudi Tedjo Setiyono (Jurnal Tanaman Industri dan Penyegar, 2011)
Study aimed to determine the appearance of pepper hybrids that have a level of resistance to foot rot disease (FRD) in endemic areas. Research conducted at East Lampung District, from January to December 2010. Study is divided into two activities: research on plant resistance FRD and research on the vegetative and generative characters of hybrids pepper of resistant BPB. Study of plant resistance materials used 20 numbers of hybrids pepper that are resistant to FRD disease at greenhouse level and 2 varieties as comparison. Study arranged in Randomized Complete Block Design (RCBD), with 3 replications. Disease attack percentage is calculated based on the number of plants showed FRD symptom divided by the number of plants per plot. In the study of vegetative and generative characters, plant material used 5 numbers of hybrid pepper resistant to FRD and two comparators. RCBD with 4 replications. All plants were 6 years old. The results showed that 5 numbers of hybrid pepper until age 5 still remained 100%. Plant height and canopy height LH 20-4 of pepper hybrids is higher than Natar1. Number of branches at 50 cm LH 20-4 was higher than comparator. LH 20-4 has a diameter of the canopy was higher than the length of his node Natar 1 and the highest among all treatments. Harvest fresh weight 1884.67 g LH 20-4 achieve the highest among the other hybrid pepper and higher than the comparator Natar 1 (1791.66 g), while the average harvest a comparison Petaling highest of 3448.33 g. Expected until the third crop production will remain higher than Natar 1 so that can later be released as superior varieties of resistant to FRD and high production.